Investigation of the Resistance of Protective Plates of High-Strength Concrete with Dynamic Impact - Babych, Yevgenij; Filipchuk, Sergij; Babich, Yevgen; Pahomov, Roman (International Journal of Engineering and Technology, 2018)
In the article are given the results of the test of dynamic action of protective steel-reinforced concrete slabs. The results have been confirmed, and proved the feasibility and expediency of application for their manufacture of high-strength fast-hardening concretes. Using external damper blades for supporting the slabs allows to absorb the energy of the impact of the weapon up to 30%Â  , which increases their overall resistance to dynamic influences. The use of high-strength concrete will reduce the thickness of the plates in 2 ... 3 times compared with the concrete of conventional classes.Â Â
Keywords: strength; steel; concrete; dynamic impact.